Active learning : student´s participation in their learning process - Annika Behnsen 1994- (2018)
Teachers have to consider different aspects when they prepare how to teach their students. Amongst various teaching styles, there are different methods that emphasize the students’ active participation in their learning process. Therefore, this thesis will focus on active learning and important aspects in connection to it. The aim of this essay is to give the reader a detailed overview of what active learning is. The presented information about forms, models and methods of active learning are supposed to raise the reader’s interest and awareness for the importance of students’ active participation in their learning process. Various methods, ideas and researches from different scientists are discussed in order to acquire information about the meaning of active learning and its background. Additionally, the author conducted a pilot study during an internship at an Icelandic elementary school. The aim of that study was to evaluate if students achieve better learning outcomes when they are actively involved in the learning process. The results of the thesis emphasize the importance of active learning as it helps the students to process new information better and connect them to already existing knowledge and experiences. The different aspects that are mentioned in the Icelandic National Curriculum as well as the results of the authors’ pilot study confirm these results. In addition to that, the results of this thesis show clearly that there are different forms of active learning and a variety of methods to implement it. Moreover, the different researches that were conducted in Iceland showed that 75% of the observed teaching lessons were described to be good. Nevertheless, the results of the different researches showed clearly that tuition in Iceland is mainly teacher-orientated and students are passive recipients of knowledge most of the time. Those results indicate the necessity to make a change in teaching methods. The focus should be on the students’ active participation and therefore teaching methods such as ...